2020
DOI: 10.1163/1568539x-00003585
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between personality traits and roosting behaviours suggest a behavioural syndrome in little brown bats

Abstract: Behavioural syndromes are composed of correlated suites of personality traits and can include traits related to the behaviour and ecology of free-ranging animals. We used captive little brown bats (Myotis lucifugus) to test the hypothesis that behaviours measured in standardized tests reflect personality traits and form behavioural syndromes with roosting behaviours. We predicted: (1) measured behaviours would be repeatable; (2) personality traits and roosting behaviours would form behavioural syndromes; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 90 publications
(139 reference statements)
3
19
1
Order By: Relevance
“…Contact rates in roosts are, therefore, probably higher between females than between males and females. Female bats also appear to be more selective about day roosts than males [53] and the most exploratory females, therefore, may visit, and explore, different roosts more frequently [42]. As a result, exploratory females could be exposed to more conspecifics and more contaminated substrates than less exploratory females resulting in higher infection intensity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contact rates in roosts are, therefore, probably higher between females than between males and females. Female bats also appear to be more selective about day roosts than males [53] and the most exploratory females, therefore, may visit, and explore, different roosts more frequently [42]. As a result, exploratory females could be exposed to more conspecifics and more contaminated substrates than less exploratory females resulting in higher infection intensity.…”
Section: Discussionmentioning
confidence: 99%
“…We quantified personality traits for each individual using hole-board and Y-maze tests [ 40 42 ]. Traits measured for little brown bats in both tests are repeatable within individuals across time and are correlated with ecologically relevant roosting and social behaviours [ 42 ]. Although we did not measure repeatability in this study, all personality traits measured here have previously been shown to be weakly to highly repeatable (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations